Vocabulary Size Leads to Better Attunement to L2 Phonetic Differences: Clues from Russian Learners of English. Issue 4 (1st October 2020) - Georgiou, Georgios P.; Perfilieva, Natalia V.; Tenizi, Maria
ABSTRACT: Previous research has shown that an increased second language (L2) vocabulary size leads to better attunement to the cues required to distinguish L2 contrastive phones. This has been the central tenet of the vocabulary-tuning model (vocab) on the basis of evidence by Japanese learners of English in Australia. We aim to test the validity of the aforementioned hypothesis by extending the research for learners with a different first language (L1) background and learners who do not have naturalistic access to the L2 input (i.e., learn the L2 through a controlled foreign classroom setting). To this purpose, 28 Russian speakers, who were learning English in Russia at the time, participated in two psychoacoustic tests in which they were asked to assimilate L2 vowels to their L1 phonological system and discriminate vowel contrasts respectively. The participants were divided into two groups according to their vocabulary size in English; comprising the small vocabulary (SV) and the high vocabulary (HV) groups. The results showed that the HV group demonstrated similar assimilation scores to the SV group. However, the HV group was able to perceive within-category differences and more accurately discriminate specific pairs of English vowel contrasts in comparison to the SV group. The findings are partially consistent with the central hypothesis of the Perceptual Assimilation Model-L2 and the vocab model as the expansion of L2 vocabulary was linked with better attunement to phonetic differences in the L2. Another important finding is that a more developed vocabulary results in fine-tuning to L2 phonetic differences, even in a restricted L2 learning setting [work supported by the "RUDN University Program 5–100"].